HETEROGENEOUS GROWTH IN THE NILE TILAPIA - SOCIAL STRESS AND CARBOHYDRATE-METABOLISM - Fernandes, M. D.; Volpato, G. L. (Elsevier B.V., 1993)
Increase in heterogeneous growth as a result of grouping in the Nile tilapia, Oreochromis niloticus (L.), is presumed to be partially promoted by the social stress imposed by the dominant fish on the subordinates. Such stress may decrease the energy available for growth. In this study, the effect of social stress on carbohydrate metabolism was studied in adult, growing males. All animals were deprived of food during the experimentation period and pairing was imposed for either 2 or 4 days. Glycemia was measured before and after pairing, and muscle and liver glycogen contents were determined only after pairing. Subordinate fish showed the highest consumption of carbohydrate reserves. This response was caused by the social stress imposed which corroborates the idea that metabolic differences promoted by social stress may be involved in the rouping effect on heterogeneous growth in the Nile tilapia.
Keywords: INTERMEDIARY METABOLISM; OREOCHROMIS-NILOTICUS; NILE TILAPIA; HETEROGENEOUS GROWTH; GROWTH DEPENSATION; GROWTH; FISH; GLYCEMIA; GLYCOGEN; CARBOHYDRATE; SOCIAL STRESS; SOCIAL DOMINANCE; BEHAVIOR